Comparison of Reliability of Norberg Angle and Distraction Index as Measurements for Hip Laxity in Dogs - Klever, Julius; Brühschwein, Andreas; Wagner, Silvia; Reese, Sven; Meyer-Lindenberg, Andrea (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective The main purpose of the study was to compare reliability of measurements for the evaluation of hip joint laxity in 59 dogs.Materials and Methods Measurement of the distraction index (DI) of the PennHIP method and the Norberg angle (NA) of the Fédération Cynologique Internationale (FCI) scoring scheme as well as scoring according to the FCI scheme and the Swiss scoring scheme were performed by three observers at different level of experience. For each dog, two radiographs were acquired with each method by the same operator to evaluate intraoperator-reliability.Results Intraoperator-reliability was slightly better for the NA compared with the DI with an intraclass correlation coefficient (ICC) of 0.962 and 0.892 respectively. The ICC showed excellent results in intraobserver-reliability and interobserver-reliability for both the NA (ICC 0.975; 0.969) and the DI (ICC 0.986; 0.972). Thus, the NA as well as the DI can be considered as reliable measurements. The FCI scheme and the Swiss scoring scheme provide similar reliability. While the FCI scheme seems to be slightly more reliable in experienced observers (Kappa FCI 0.687; Kappa Swiss 0.681), the Swiss scoring scheme had a noticeable better reliability for the unexperienced observer (Kappa FCI 0.465; Kappa Swiss 0.514).Clinical Significance The Swiss scoring scheme provides a structured guideline for the interpretation of hip radiographs and can thus be recommended to unexperienced observers.
Keywords: canine hip dysplasia; distraction index; Norberg angle; radiography